2010
DOI: 10.1179/174328509x431472
|View full text |Cite
|
Sign up to set email alerts
|

The reducibility of the Greek nickeliferous laterites: a review

Abstract: This paper refers to a critical review of the Greek nickeliferous laterites roasting reduction studies for better understanding of the process thermodynamic and kinetic mechanisms, affecting decisively the smelting step in pyrometallurgical extraction of nickel from these ores. From this work, it is deduced that iron and nickel oxide reduction degree does not exceed 33 and 76% respectively, the reductive reactions being stopped within the first 20-30 min. Thus, part of ferric iron is transformed into ferrous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…Zevgolis et al [13] reviewed the physicochemical properties of the reduction roasting of Greek laterite ores. The researchers concluded that the reduction degrees of the iron and nickel oxides in Greek laterites between 700 to 900 • C could not exceed 33% and 76%, respectively, even though adequate amounts of carbon remained in the calcine.…”
Section: Reduction Roast and Upgradementioning
confidence: 99%
“…Zevgolis et al [13] reviewed the physicochemical properties of the reduction roasting of Greek laterite ores. The researchers concluded that the reduction degrees of the iron and nickel oxides in Greek laterites between 700 to 900 • C could not exceed 33% and 76%, respectively, even though adequate amounts of carbon remained in the calcine.…”
Section: Reduction Roast and Upgradementioning
confidence: 99%
“…In addition, through the pre-reduction, the ratio of Ni to Fe can be controlled in order to obtain an appreciable grade of Fe-Ni alloys with high nickel recovery (Diaz et al, 2004;Rigopoulos et al, 2004;Solar, 2008, 2009Zevgolis et al, 2009. Furthermore, the problem posed by the presence of MgO and SiO 2 contents is that they significantly affect the degree of pre-reduction, as well as the operating temperature used in subsequent steps of the process.…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, reaching the highest degree of reduction is of decisive importance as it corresponds to quite a high energy saving during the smelting step, 6,10,11 and it also ensures a quiescent process in the EF since no reduction gases are evolved in the slag. 6 Although coal is industrially the most commonly used reductant, most studies have focused on the gaseous reduction of laterites. 9,[12][13][14][15] In the current study, the mineralogy of Sivrihisar limonitic ore as well as its reduction behaviour has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases an intermediate type, also known as nontronite, is also included in this classification. 6 The history of nickel in Turkey goes back to the late 1970s when the first laterite deposit was discovered at Ç aldag. 7 The other commercially important lateritic deposits of Turkey are Gö rdes, Banaz and Sivrihisar.…”
Section: Introductionmentioning
confidence: 99%